Power Plants, Steam and Gas Turbines WebQuest - Carlos Ulloa; Guillermo D. Rey; Ángel Sánchez; Ángeles Cancela (MDPI AG, 2012)
A WebQuest is an Internet-based and inquiry-oriented learning activity. The aim of this work is to outline the creation of a WebQuest entitled "Power Generation Plants: Steam and Gas Turbines." This is one of the topics covered in the course "Thermodynamics and Heat Transfer," which is offered in the second year of Mechanical Engineering at the Defense University Center at the Naval Academy in Vigo, Spain. While participating in the activity, students will be divided into groups of no more than 10 for seminars. The groups will create PowerPoint presentations that include all of the analyzed aspects. The topics to be discussed during the workshop on power plant turbines are the: (1) principles of operation; (2) processes involved; (3) advantages and disadvantages; (4) efficiency; (5) combined cycle; and (6) transversal competences, such as teamwork, oral and written presentations, and analysis and synthesis of information. This paper presents the use of Google Sites as a guide to the WebQuest so that students can access all information online, including instructions, summaries, resources, and information on qualifications.